Examining the Impact of Video Feedback on Instructor Social Presence in Blended Courses - Borup, Jered; West, Richard E.; Thomas, Rebecca A.; Graham, Charles R. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
This mixed method research examined instructors’ use of video feedback and its impact on instructor social presence in 12 blended sections of three preservice educational technology courses. An independent samples t-test was conducted and found no significant difference in perceptions of instructor social presence between students who received video feedback (M = 5.77, SD = 0.85) and those who received text (M = 5.62, SD = 0.75); t(178) = 1.23, p = 0.22. The analysis of 22 student and nine teacher interviews found that participants generally viewed video feedback to be more effective at establishing instructor social presence because instructors could better speak with emotions, talk in a conversational manner, and create a sense of closeness with students. Students also explained that the blended learning format lessened the impact of video feedback on instructor social presence, which may help to explain why statistical differences were not found.